Toward uniform electrodeposition of magnetic Co-W mesowires arrays: direct versus pulse current deposition. (10th January 2016) - Tsyntsaru, N.; Silkin, S.; Cesiulis, H.; Guerrero, M.; Pellicer, E.; Sort, J.
Abstract: Template-assisted electrodeposition of Co-rich Co-W alloys into mesoporous anodized aluminum oxide from ammonia-free solutions is investigated. The optimum deposition conditions rendering uniform filling of the pores, either by direct current (DC) or pulse current (PC) methods, are established. Contrary to the DC deposition on flat surfaces (which is kinetically controlled), the DC electrodeposition in the mesopores of the template is limited by mass transfer. Conversely, under PC mode, the Co-W electrodeposition process is controlled by kinetics at frequencies > 0.3 Hz; and by diffusion at lower frequencies. The obtained mesowires are nanocrystalline and exhibit a hexagonal closed packed (hcp) structure. The magnetic properties of selected Co-W mesowires, with variable aspect ratio, are also studied. The arrays of mesowires exhibit a semi-hard ferromagnetic behavior with coercivity values that surpass those of Co mesowires with similar dimensions. The interplay between interwire dipolar interactions, magnetocrystalline anisotropy and shape anisotropy on the overall shape of the hysteresis loops (in particular, on the coercivity and squareness ratio values, as well as on the effective magnetic easy axis direction) is investigated in a semiquantitative manner.